Experimental Study of The Effect of Activator Molarity on The Compressive Strength of Fly Ash-Based Geopolymer Concrete from Bengkayang Regency Power Plant - Faraid, Luthi Armey; Herwani, Herwani; Faisal, Faisal; Parabi, Ashraf Dhowian (Jurnal Teknik Sipil, 2024)
Geopolymer concrete is a form of concrete where Portland cement is substituted with alternative materials like fly ash, rice husk ash, and other silica- and aluminum-rich sources as binders. The research employed an experimental method by preparing geopolymer concrete test specimens using fly ash, NaOH solution, Naâ‚‚SiOâ‚ƒ, fine aggregate, and coarse aggregate. Tests conducted included physical properties (slump test and unit weight) and mechanical properties (compressive strength, split tensile strength, and modulus of elasticity). The results showed a slump range of 130"“190 mm, an average unit weight between 2249.39 kg/m ³ and 2336.39 kg/m ³, a 28-day average compressive strength between 12.32 MPa and 15.92 MPa, an average split tensile strength between 1.46 MPa and 1.56 MPa, and an average modulus of elasticity (Chord Modulus) between 3011.67 MPa and 3881.8 MPa. The optimal variation was achieved with an NaOH solution concentration of 10 M, resulting in a slump of 160 mm, a 28-day average compressive strength of 15.92 MPa, an average split tensile strength of 1.56 MPa, and an average modulus of elasticity (Chord Modulus) of 3881.48 MPa. Therefore, fly ash-based geopolymer concrete demonstrates potential as a viable substitute for cement as a binder material.